The role of quintuple helix on halal-tourism ecosystem in Indonesia - Sri Herliana; Syifaya Qorina (Proceeding International Conference on Accounting and Finance, 2024)
Purposes: The Covid-19 pandemic gives a negative impact to muslim travel market as the trend drop dramatically for two period (2020 &2021). After that, as GMTI reported, the trend not only increase gradually, but also projected to reach 230 million arrivals. And the majority of the muslim traveller come to Indonesia as their preferred destination, that make Indonesia lies in the first stage of the Destination Ranks. Therefore, it is crucial for all actors in Indonesia to maintain and improve continually this achievement. And this paper aims to promote an approach through Quintuple Helix in Halal-Tourism Ecosystem. This Ecosystem involves five variables, such as; education system, economic system, natural system, media system, and political system. Methods: The method used in this analysis is qualitative descriptive Findings: As the result, the interconnected between education system, economic system, natural system, media system, and political system is predicted to strengthen the halal-tourism ecosystem. Practical Implication: This research will give some input to those variables in ecosystem, such as higher investment in education system and science, emphasis on halal-tourism business, protecting and maintaining its heritage to attract muslim market, creating brand image for halal tourism, and input recommendation for the government. Originality/Novelty: This paper conducts research that give new perspective to halal-tourism through quintuple helix. Several researches have been done by using different perspective such as penta-helix method and in specific destinations.